Karunia Menasehati Dalam Konseling Pastoral - Adiyati, Rini; Wahyu, Yuli (Jurnal Kala Nea, 2021)
Pastoral counseling services have an important role in building the Body of Christ. The congregation in general needs guidance, restoration and life changes to be served well. This study aims to analyze the problems that occur in the scope of pastoral counseling, especially related to empowering the gift of counseling. The author uses a qualitative method to get details of the problem, and find the right steps to answer the problem. The results of the study found that the congregation's need for pastoral counseling services, especially related to the gift of counseling, is very high, where many congregations need special assistance in dealing with their problems.